MIDWIFERY CARE FOR FIRST TRIMESTER PREGNANT WOMEN WITH PAINFUL EATING DUE TO GASTRIC ACID: Keywords: Gestational GERD, First Trimester, Midwifery Care, Progesterone, Dietary Intolerance. - listisari, listisari panjaitan; al husnah, Nazla; Manik, Nessy Supianti; hutabarat, Dewi sartika; Simarmata, Mesrida (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Gastroesophageal reflux disease (GERD) and acute gastritis affect up to 80% of pregnancies, predominantly escalating during the first trimester due to profound endocrine shifts. If left unmanaged, severe dietary intolerance leads to maternal malnutrition, dehydration, and fetal growth restriction (FGR). Objective: This study aims to criticaly analyze evidence-based midwifery clinical management for a first-trimester primigravida presenting with severe odynophagia and rice-induced dyspepsia driven by gestational acid dysregulation. Methods: A comprehensive, single-case clinical study was conducted utilizing the synchronized 7-step Helen Varney framework integrated with Basic Midwifery Sciences (Genetics, Microbiology, Biophysics, and Pharmacology). Results: Advanced pathophysiological profiling revealed that progesterone-induced lower esophageal sphincter (LES) hypotonia combined with mechanical intragastric pressure shifts precipitated severe mucosal irritation. Microbiological screening ruled out Helicobacter pylori exacerbations. Implementation of micro-portion texturized dietary substitution (replacing solid rice with thermal-stabilized soft porridge), postural anti-reflux dynamics, and cautious, calibrated administration of non-systemic antacids synchronized with Vitamin B6 successfully eradicated epigastric burning and restored optimal nutritional kinetics. Conclusion: Synergistic midwifery models combining biomolecular clinical awareness with customized non-pharmacological dietary physics demonstrate high efficacy in preventing gestational cachexia and ensuring excellent maternal-fetal outcomes.